Employment responses to income effect: Evidence from pension reform - Sebastian Becker; Hermann Buslei; Johannes Geyer; Peter W. de Haan (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
For the design of the pension system, it is crucial to disentangle the employment responses related to the substitution effect and the income effect. In this paper, we provide causal evidence regarding the importance of the income effect, which is generally assumed to be small or non-existent. We exploit a pension reform in Germany that raised pension bene- fits related to children. For the identification, we exploit the discontinuity induced by the reform: only mothers with children born before 1.1.1992 were affected by the pension reform. Children born after this cut-off date did not change pension income. We use a difference-in-differences estimator based on administrative data from the German pension insurance that includes complete individual employment histories. We find that income effects are significant and economically important. We show that the policy led to a reduction in the employment of affected females. Further, we are able to show effect heterogeneity on different dimensions: by treatment intensity, age of the mother, and pre-reform pension wealth.
Keywords: 330